The Effect of Fermented Rice Bran-Based Feed on Production Performance of Meat Ducks - Rina Kurniawati; Michael Thompson (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
The increasing cost of commercial feed has encouraged the exploration of alternative feed resources for poultry production. Rice bran is widely available in many agricultural regions but its utilization is limited due to high fiber content and the presence of anti-nutritional factors. Fermentation technology has been proposed to improve its nutritional quality and digestibility. This study aimed to analyze the effect of fermented rice bran-based feed on the production performance of meat ducks. The research applied an experimental design using four feed treatments with different levels of fermented rice bran inclusion. Parameters observed included feed consumption, body weight gain, and feed conversion ratio. Data were analyzed using analysis of variance followed by Duncan's multiple range test. The results showed that fermented rice bran significantly improved feed efficiency and body weight gain compared with conventional feed formulations. Ducks receiving diets containing fermented rice bran demonstrated better nutrient utilization and improved growth performance. These findings confirm that fermentation can enhance the nutritional value of rice bran and support sustainable duck production systems. The study contributes to the development of alternative feed strategies using locally available agricultural by-products.